The Impact of Internal Governance on Conservatism: Evidence from Australia - Liew, Millie; Cao, June (American Accounting Association, 2023)
Financial reporting decisions can be influenced by the distribution of executive decision-making power. We examine whether internal governance, the process through which the power to make decisions is distributed between CEOs and their subordinates, can influence the level of conservatism in such decisions. We show that firms with better internal governance are more conservative. We also find that the effect is more pronounced for firms with less powerful and older CEOs, those with subordinate executives who contribute more, and those who are more mature. We conduct various tests that confirm the robustness of our results. Unlike other studies that focus only on CEOs, we examine how the top management team as a group and the power distribution between CEOs and key subordinates shape financial reporting quality. Our study can inform various stakeholders, including firms aiming to appoint executives and strengthen their internal governance.